Fate and toxicity of triclosan in tidal flow constructed wetlands amended with cow dung biochar. (January 2023) - Suthar, Surindra; Chand, Naveen; Singh, Vineet
Abstract: Triclosan (TC) is one of the threats to the environment due to its bioaccumulative nature, persistency, combined toxicity in aquatic biota, and endocrine-disrupting nature. This study revealed the removal of TC via three distinct setups of vertical flow constructed wetlands (VFCW: B-VFCW (with biochar); PB-VFCW (with plant Colocasia and biochar); C-VFCW (without biochar but with plant)) operated with normal flow and tidal-flow (flooding/drying cycles of 72 h/24 h: B-TFCW; PB-TFCW; C-TFCW) mode for 216 h of the operation cycle. The effluent was analyzed for changes in TC load and wastewater parameters (COD, NO3 –N, NH4 + -N, and DO). TC reduction efficiency (%) was found to be higher in PB-TFCW (98.41) followed by, C-TFCW (82.41), B-TFCW (77.51), PB-VFCW (71.83), C-VFCW (64.25), and B-VFCW (52.19) ( p  < 0.001). Reduction efficiency for COD (29-75 – 53.10%), and NH4 + -N (86.5–97.9%) was better in TFCWs than that of setups with a normal mode of operation. TFCWs showed higher DO (3.87–4.89 mg L −1 ) during the operation period than that of VFCWs. The toxic impact of TC in plant stand was also assessed and results suggested low phototoxic and oxidative enzyme activities (catalase, CAT; superoxide dismutase, SOD; hydrogen peroxide, H2 O2 ; malondialdehyde, MDA) in TFCWs. In summary, biochar addition and tidal flow operation played a significant role in oxidative- and microbial-mediated removals of TC in wastewater. This study provides an alternative strategy for the efficient removals of TC in constructed wetland systems and new insights into the toxic impact of pharmaceuticals on wetland plants. Graphical abstract: Image 1 Highlights: Triclosan removals was improved by biochar (BC) addition in CWs. Tidal flow operation showed better removals than vertical flow mode. Combination of plant and BC showed highest TC removals. CW operation modification shifts the oxidative stress and phototoxicity in plants.